Minat Kunjungan Wisatawan Museum Gunungapi Merapi - Suharto (Media Wisata, 2019)
This paper is based on exploratory studies conducted at the Merapi Volcano Museum (MGM) with the aim of finding out the factors that influence interest in tourist visits. The methodology used in this study is based on field studies, through observation instruments, interviews, and questionnaires. The research respondents were domestic tourists who were taken randomly, the snippet technique as the primary data source was several museum employees and managers. The factors of tourist interest are identified through three things, namely the attraction of objects, accessibility and amenities.The results of the study found that the three main factors driving tourists' interest in visiting the Merapi Volcano museum were mainly due to the presence of amenities, especially in the provision of vast parking lots, the presence of new Merapi Park destinations, the presence of toilets and the existence of various tourist facilities typical of Kaliurang. The existence of the facilities provided by this management has been responded positively by the tourists as expected by management